Hatobangon: Character Building and Revitalization of Cultural Values in Panyabungan - Rangkuti, Suheri Sahputra; Muslimin Hutapea; Nurintan Muliani Harahap; Eko Sumadi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
Theoretically, the culture that is still running in a group is a sign that cultural actors still play a role in the midst of society. In this context, cultural moral values and actions should also color the cultural group. It is different in Panyabungan, although Panyabungan is known as a district that is thick with nuances of customs, some of the people in Panyabungan do not describe a community with character in accordance with local cultural values and moral actions. This article was written in order to see how hatobangon's role in guiding the character of the community in Panyabungan. The research method used in this article is filed research with a descriptive-qualitative approach then the data is analyzed reductively. The results of this study found that hatobangon in guiding the character of the community in Panyabungan was only limited through traditional ceremonial containers. Meanwhile, in revitalizing customary values, hatobangon only socializes customary values in the community in their daily associations. In conclusion, hatobangon in its role in guiding the character of indigenous peoples in Panyabungan needs wider space for movement and government involvement.